SINERGI TRANSFORMASI DIGITAL DAN KEPEMIMPINAN SPIRITUAL: MEMBANGUN PARADIGMA BARU MANAJEMEN PENDIDIKAN YANG ADAPTIF DAN BERKARAKTER DI ERA RI 4.0 DAN SOCIETY 5.0 - Lilik Hidayat Pulungan (Hijri, 2025)
digital transformation to maintain relevance and quality. However, the widespread adoption of technology without a foundation in values often neglects character formation. This study aims to formulate a synergy model between digital transformation and spiritual leadership in educational management. Using a library research method with a comprehensive analysis of various policy documents and research journals related to curriculum management, educational digitalization, and spiritual leadership, the study's results indicate that digital transformation in Islamic and general education management is not merely limited to the use of technological devices, but requires a repositioning of leadership that emphasizes spiritual values (integrity, empathy, and divine vision). This synergy produces a management paradigm that is adaptive to technological change while remaining robust in shaping student character. Proposed strategies include the development of a humanistic technology-based curriculum, the implementation of microlearning to improve teacher competency, and the revitalization of traditional values within the digital ecosystem